2009
DOI: 10.1007/s10584-009-9667-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spatial resolution on area burned and fire occurrence projections in Portugal under climate change

Abstract: In this study, we investigated the impact of future climate change on fire activity in 12 districts across Portugal. Using historical relationships and the HIRHAM (High Resolution Hamburg Model) 12 and 25 km climate simulations, we assessed the fire weather and subsequent fire activity under a 2 × CO 2 scenario. We found that the fire activity prediction was not affected by the spatial resolution of the climate model used (12 vs. 25 km). Future area burned is predicted to increase 478% for Portugal as a whole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 43 publications
5
74
1
4
Order By: Relevance
“…This 3.7 times increase is translated into shorter fire rotation periods which is in agreement with the results obtained in other approaches carried out in the Iberian Peninsula. In Portugal, Carvalho et al (2010) reported even greater values than the ones used in this work with an increment of 478% (> 5.7 times the current level) for the SRES A2 scenario. A simulation analysis performed in three areas of NE Spain show that currently fuel-humidity limited regions could suffer a drastic shift of fire regime with an up to 8 times increase of annual burned area while the impact is predicted to be less pronounced in drier areas (Loepfe et al, 2012).…”
Section: Fire Regime Estimates and Forest Changescontrasting
confidence: 50%
See 1 more Smart Citation
“…This 3.7 times increase is translated into shorter fire rotation periods which is in agreement with the results obtained in other approaches carried out in the Iberian Peninsula. In Portugal, Carvalho et al (2010) reported even greater values than the ones used in this work with an increment of 478% (> 5.7 times the current level) for the SRES A2 scenario. A simulation analysis performed in three areas of NE Spain show that currently fuel-humidity limited regions could suffer a drastic shift of fire regime with an up to 8 times increase of annual burned area while the impact is predicted to be less pronounced in drier areas (Loepfe et al, 2012).…”
Section: Fire Regime Estimates and Forest Changescontrasting
confidence: 50%
“…The fire regime represents a particular combination of fire 2 ranean basin (Moriondo et al, 2006;Lung et al, 2013) while several studies concerning the Iberian Peninsula, point to an increment in fire risk under future climate scenarios (e.g. Moreno, 2005;Carvalho et al, 2010, Vázquez et al, 2012. This possible increase in fire activity could have important effects on forest landscapes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nitschke & Innes 2008) or to use RCM with higher spatial resolution (e.g. Pereira et al 2002, Durão & Corte-Real 2006, Carvalho et al 2010. Alternatively, each model performance can be evaluated and, for instance, the inter-comparison of the model-based projections for the new IPCC emissions scenarios points out that the MIROC models have a small decrease (~10%) in spring precipitation and a rise of 4°C in mean spring temperature during the 2070−2099 period, in Southern Europe and Northern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Carvalho et al (2010) investigated the impact of future climate change on fire activity in 12 districts across Portugal using historical relationships and simulations of the High Resolution Hamburg Model (HIRHAM). They have estimated an increase of 280% in the number of fires and of 480% in burnt area for all 12 districts in the case of a 2× CO 2 scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation